2020
DOI: 10.1083/jcb.201910064
|View full text |Cite
|
Sign up to set email alerts
|

α-Tubulin detyrosination impairs mitotic error correction by suppressing MCAK centromeric activity

Abstract: Incorrect kinetochore–microtubule attachments during mitosis can lead to chromosomal instability, a hallmark of human cancers. Mitotic error correction relies on the kinesin-13 MCAK, a microtubule depolymerase whose activity in vitro is suppressed by α-tubulin detyrosination—a posttranslational modification enriched on long-lived microtubules. However, whether and how MCAK activity required for mitotic error correction is regulated by α-tubulin detyrosination remains unknown. Here we found that detyrosinated α… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…In agreement, stimulation of kinetochore microtubule dynamics in otherwise chromosomally unstable cancer cells by increasing Kinesin-13 depolymerase activity reestablished chromosomal stability [55,74]. Building on the previous finding that MCAK´s microtubule depolymerizing activity is reduced four fold in the presence of detyrosinated microtubules in vitro [75,76], it was recently shown that the mitotic error correction activity of MCAK and Kif2b is regulated by α-tubulin detyrosination [37]. Accordingly, experimental depletion of TTL or overexpression of VASH1-SVBP, which caused a constitutive increase of α-tubulin detyrosination in the vicinity of the kinetochores, compromised error correction, leading to chromosome segregation errors.…”
Section: • a Mitotic Error Codesupporting
confidence: 66%
See 3 more Smart Citations
“…In agreement, stimulation of kinetochore microtubule dynamics in otherwise chromosomally unstable cancer cells by increasing Kinesin-13 depolymerase activity reestablished chromosomal stability [55,74]. Building on the previous finding that MCAK´s microtubule depolymerizing activity is reduced four fold in the presence of detyrosinated microtubules in vitro [75,76], it was recently shown that the mitotic error correction activity of MCAK and Kif2b is regulated by α-tubulin detyrosination [37]. Accordingly, experimental depletion of TTL or overexpression of VASH1-SVBP, which caused a constitutive increase of α-tubulin detyrosination in the vicinity of the kinetochores, compromised error correction, leading to chromosome segregation errors.…”
Section: • a Mitotic Error Codesupporting
confidence: 66%
“…Similar to dynein/dynactin, kinesin-5 appears to have increased affinity to tyrosinated dendritic microtubules in neurons [80], but direct evidence from in vitro reconstitution assays is still lacking. Nonetheless, recent work in which centrosome positioning in human mitotic cells was tracked in 3D indicated that centrosome separation at nuclear envelope breakdown is insensitive to the tyrosinated state of -tubulin [37]. This reinforces the idea that the observed increase in mitotic errors associated with excessive αtubulin detyrosination is due to the incapacity to correct, rather than an increased propensity to make errors.…”
Section: • a Mitotic Error Codesupporting
confidence: 57%
See 2 more Smart Citations
“…Other tubulin PTMs have been shown to impact mitotic progression and may also underlie cancer phenotypes. Recent work has shown that a disruption of α-tubulin detyrosination leads to reduced chromosome congression and increased errors of kinetochore-microtubule attachment (60–63). Further investigations into tubulin PTMs and their modifying enzymes are required to understand the nuanced interaction between histone and tubulin modifications in cells and the implications for cancer progression.…”
Section: Discussionmentioning
confidence: 99%